Insertar en el código orgánico integral penal nuevos delitos en contra del medio ambiente y la Naturaleza o Pacha Mama - Jaramillo Abad, James Edmundo (2016)
The Constitution of the Republic of Ecuador made a double recognition of rights of Ecuadorians live in a healthy environment, in its article 14 that recognizes as good right to live, and in the article 66 paragraph 27 as one of the rights of freedom. These rules of constitutional order and the recognized in international legal instruments, confirming the importance of the environment, as one of the fundamental rights of citizens. However, as in many other cases, there are unlawful behaviors against the environment, which are provided for in the organic comprehensive Ecuadorian criminal code under the heading of offences against the environment and nature or Pacha Mama, with typing in our country these behaviors is to ensure the observance of the fundamental right. Chapter IV crimes against the environment or Pacha Mama, in the comprehensive code of criminal, criminalizes and penalizes some behaviors that go against the environment, but as nature and man are dialectic, currently there are cases and circumstances that warrant an increase in these typical behaviors, this way may be appointed several conduct contrary to the environmental sector have not been provided for in the criminal norm : non-compliance with environmental plans referred to in environmental studies approved by the Ministry of the environment; exploitation of minerals of illegally; excessive noise caused by industries and vehicles; the pollution of the atmosphere because of combustion engines; failure to adopt good environmental practices in companies, governmental organizations and non-governmental, the deposit of organic and inorganic wastes, biohazardous, radioactive, among others places not allowed, etc., these and other types must be controlled through law, in this way avoiding the imbalance of nature and the deterioration of the quality of life. The comprehensive Penal Organic Code criminalizes and penalizes some behaviors that go against the environment, but as nature and man are dialectic, currently there are cases and circumstances that warrant an increase in these typical behaviors, in this way you can for example mention production activities: storage, traffic, import or export, transport, abandonment, scrap, shock, or perform any other activity with dangerous substances corrosive characteristics reactive, explosive, toxic, flammable, radioactive or other similar, the exploitation of animals to obtain economic means or fun, the destruction of habitat or ecosystem home to animal species, etc., these and other types must be controlled through law, since does not occur may result in the extermination of the man himself. Therefore, in accordance with our Constitution which stipulates the protection of the environment and as a civil right of the Ecuadorian people to live in a healthy, balanced environment and pollution as a primary duty of the State. We must not forget that the world and society evolve constantly, so that crimes against the environment and nature must also be updated on an ongoing basis, so that it la norme and punish properly and in compliance with the proportionality of the offence committed.